Extremely Stretchable and Fast Self‐Healing Hydrogels. Issue 23 (9th April 2016) - Jeon, Insu; Cui, Jiaxi; Illeperuma, Widusha R. K.; Aizenberg, Joanna; Vlassak, Joost J.
Abstract : Dynamic crosslinking of extremely stretchable hydrogels with rapid self‐healing ability is described. Using this new strategy, the obtained hydrogels are able to elongate 100 times compared to their initial length and to completely self‐heal within 30 s without external energy input.